Relevansi Konsep Filsafat Jiwa Tazkiyyatun Nafs Imam Al Ghazali terhadap Degradasi Moral Generasi Hari Ini - Taufiqurrahman Efendi; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the relevance of the educational concept of tazkiyyatun nafs Imam Al-Ghazali to students. The research method used is a qualitative type through literature study. The results and discussion of this research are that Al-Ghazali taught humans to be able to put off mental illness and adorn the soul with means of soul purification. The impurities of the soul that are inherent in humans are stomach and genital lust, verbal disaster, anger, envy and jealousy, love of the world, love of wealth and misery in the human soul as well as in the education of Imam al-Ghazali at a young age and that is not absolute. In this case, the book Ihya Ulumuddin as a book that combines fiqh and Sufism presents the concept of taqwa namely, following Allah's commands and avoiding His prohibitions, eliminating heart disease, and leading in good and wise social interactions with others. After trying to suppress or minimize a person's despicable actions, he should adorn himself with commendable deeds, this is what is called tahall.